Inovasi INOVASI PJOK DARI LIMBAH UNTUK MENINGKATKAN MOTIVASI BELAJAR DAN GERAK DASAR SISWA SD: LITERATURE REVIEW - Saneraro Ahcre Kafiar; Edwita; Dina Rahmi Darman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study presents a literature review on the development of manipulative learning aids for Physical Education, Sports, and Health (PJOK) at the elementary school level, utilizing waste and recycled materials. The review synthesizes findings from 23 relevant articles to identify needs and assess the effectiveness of waste-based learning aids in enhancing fundamental movement skills specifically throwing and catching as well as the learning motivation of third-grade elementary students. Findings consistently indicate that modified aids made from waste materials (such as soft balls crafted from fabric scraps, foam, and waste paper) significantly increase student participation, reduce the fear of injury, and improve basic motor skill outcomes. The novelty of this research lies in its emphasis on a project-based participatory approach, wherein students act not merely as users but as active participants in assembling the learning aids from these waste materials. This approach is grounded in constructivist theory (Piaget, Vygotsky) and experiential learning theory (Kolb), positioning the process of developing the media itself as a meaningful learning experience.